2004
DOI: 10.1901/jaba.2004.37-111
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Reading Interventions: Generalization Across Instructional Strategies, Time, and Passages

Abstract: This study examined the generalized effects of three treatment conditions (performance based, skill based, and a combination of the two) on oral reading fluency by an elementary school student. Results indicated equal effectiveness of all treatments, maintenance, and possible evidence of generalization across passages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Less intrusive treatment packages were directly compared with more complex treatments. Similar to results of other studies, individual differences were found across students, in that various combinations of antecedent and consequential components were effective (Bonfiglio, Daly, Martens, Lin, & Corsaut, 2004;Eckert et al, 2002). Rachel responded best to a treatment package that contained a combination of instructional and reward components.…”
Section: Discussionsupporting
confidence: 84%
“…Less intrusive treatment packages were directly compared with more complex treatments. Similar to results of other studies, individual differences were found across students, in that various combinations of antecedent and consequential components were effective (Bonfiglio, Daly, Martens, Lin, & Corsaut, 2004;Eckert et al, 2002). Rachel responded best to a treatment package that contained a combination of instructional and reward components.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, a large WCPM gain score helps to demonstrate that the student learned to read practiced material more fluently and could apply (i.e., generalize) that learning to previously unread text. The retention passage gains reflect students' learned fluency over time (i.e., approximately 2 days), which is also important as a form of generalized learning (Bonfiglio, Daly, Martens, Lin, & Corsaut, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Performance feedback typically is provided by the researcher telling the student the number of words he or she read correctly or incorrectly in one minute at the end of a reading, and showing the student the results displayed on a graph (Bonfiglio, et al, 2004;Eckert et al, 2000Eckert et al, , 2002Eckert, Dunn, & Ardoin, 2006).…”
Section: Hypothesis 1: Motivationmentioning
confidence: 99%